Mitochondria-associated endoplasmic reticulum membranes and cardiac hypertrophy: Molecular mechanisms and therapeutic targets - Luan, Yi; Jin, Yage; Zhang, Pengjie; Li, Hongqiang; Yang, Yang (Frontiers in Cardiovascular Medicine, 2022)
Cardiac hypertrophy has been shown to compensate for cardiac performance and improve ventricular wall tension as well as oxygen consumption. This compensatory response results in several heart diseases, which include ischemia disease, hypertension, heart failure, and valvular disease. Although the pathogenesis of cardiac hypertrophy remains complicated, previous data show that dysfunction of the mitochondria and endoplasmic reticulum (ER) mediates the progression of cardiac hypertrophy. The interaction between the mitochondria and ER is mediated by mitochondria-associated ER membranes (MAMs), which play an important role in the pathology of cardiac hypertrophy. The function of MAMs has mainly been associated with calcium transfer, lipid synthesis, autophagy, and ROS. In this review, we discuss key MAM-associated proteins and their functions in cardiovascular system and define their roles in cardiac hypertrophy. In addition, we demonstrate that MAM is a potential therapeutic target in the treatment of cardiac hypertrophy.